Arthroscopic Repair Versus Conservative Treatment for First-time Anterior Shoulder Dislocation - Lei, Dengqiang; Tang, Bo; Li, Yongjuan; Fan, Cheng (International Journal of Sports Medicine, 2022)
To systematically compare the clinical efficacy of conservative treatment and arthroscopic one-stage repair for patients with first-time anterior dislocation of the shoulder. A retrieval and systematic review of randomized controlled studies of primary anterior shoulder dislocation with conservative versus arthroscopic repair was conducted and further pooled analysis was performed to compare the overall difference in clinical outcomes, including redislocation and revision surgery rates, shoulder function scores and related complications. Preliminary meta-analysis showed that the risk of anterior shoulder redislocation was 4.73-fold higher in patients treated conservatively than those undergoing arthroscopic repair (RR:4.73 [2.95–7.58], p<0.000; I2=0%, p=0.920),and that the revision surgery rate was 5.91 times higher in the conservative group than in the arthroscopic repair group (RR:5.91 [2.82–12.39], p<0.000; I2=0%, p=0.560).Early arthroscopic repair can significantly reduce the redislocation and revision surgery rates and also improve the shoulder joint function score, without serious complications. However, it is necessary to recognize the subset of patients with a higher risk of redislocation in young patients through a high quality, blinded, prospective cohort study when early arthroscopic repair intervention in this subset of high-risk patients will be of significant clinical value.
Keywords: first-time anterior shoulder dislocation; arthroscopy; conservative treatment